2001
DOI: 10.1177/104973150101100501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an Educational Intervention With Relatives of Persons in the Early Stages of Alzheimer’s Disease

Abstract: The objective of this article was to describe the results of an educational intervention for family caregivers of persons in the early stages of Alzheimer's disease. A total of 58 family caregivers participated in this intervention, which consisted of five weekly educational sessions about the disease and various aspects of caregiving. Measures of knowledge about Alzheimer's disease, reactions to patients'impairments, and levels of depression at pretest, posttest, and follow-up at 9 months posttest were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…In two studies, knowledge did not seem to impact caregiver depression levels or health status [17,18]. Some studies have found no relationship between the level of knowledge and the level of caregiver burden [5,17]. However, Coen et al [15] found that the majority of their caregiver participants had an increased knowledge of dementia after the intervention.…”
Section: Benefits Of Knowledgementioning
confidence: 99%
See 4 more Smart Citations
“…In two studies, knowledge did not seem to impact caregiver depression levels or health status [17,18]. Some studies have found no relationship between the level of knowledge and the level of caregiver burden [5,17]. However, Coen et al [15] found that the majority of their caregiver participants had an increased knowledge of dementia after the intervention.…”
Section: Benefits Of Knowledgementioning
confidence: 99%
“…In two studies, knowledge did not seem to impact caregiver depression levels or health status [17,18]. Some studies have found no relationship between the level of knowledge and the level of caregiver burden [5,17].…”
Section: Benefits Of Knowledgementioning
confidence: 99%
See 3 more Smart Citations